2015
DOI: 10.1186/s12885-015-1207-z
|View full text |Cite
|
Sign up to set email alerts
|

Luminal B subtype: A key factor for the worse prognosis of young breast cancer patients in China

Abstract: BackgroundThe prognoses of young breast cancer patients are poor. The purpose of this study is to evaluate the different characteristics and prognoses among different subtypes of young breast cancer patients.MethodsThe study included 1360 patients <40 years-old (y) and 3110 patients 40-50y with operable breast cancer in Shanghai Cancer Center, Fudan University. The characteristics, overall survival (OS) and disease-free survival (DFS) were compared.ResultsThe median follow-up was 54.1 months. More grade III tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 25 publications
4
40
2
Order By: Relevance
“…The observed survival pattern is very similar to that found in a large retrospective Chinese study in which young patients with Luminal B tumors exhibited a significantly worse OS. 29 On multivariate analysis, and in contrast with what was seen for DFS, age was not a factor significantly related with OS. This might be explained by the fact that the difference in DFS rates was driven not only by Luminal B tumors, but also by Luminal A and HER2+ disease, which have previously shown to have higher relapse rates in young women.…”
Section: A N U S C R I P Tmentioning
confidence: 79%
See 1 more Smart Citation
“…The observed survival pattern is very similar to that found in a large retrospective Chinese study in which young patients with Luminal B tumors exhibited a significantly worse OS. 29 On multivariate analysis, and in contrast with what was seen for DFS, age was not a factor significantly related with OS. This might be explained by the fact that the difference in DFS rates was driven not only by Luminal B tumors, but also by Luminal A and HER2+ disease, which have previously shown to have higher relapse rates in young women.…”
Section: A N U S C R I P Tmentioning
confidence: 79%
“…This might be explained by the fact that the difference in DFS rates was driven not only by Luminal B tumors, but also by Luminal A and HER2+ disease, which have previously shown to have higher relapse rates in young women. 28,29 However, while both Luminal A and HER2+ tumors have a higher risk of recurrence, the lack of effect on survival can be attributed to the excellent response to treatment and the prolonged survival of these two subtypes in the metastatic setting. 31 The worse survival found in Luminal B disease may be related to adherence to hormonal treatment, which has been shown to be poor in young, non-white women.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Prognosis was predicted to be worse for patients in groups B and C, characterized by chromosome instability, than in luminal A patients, a finding that could be consistent with the poor prognosis of young patients. 57 Group C demonstrated highly activated immune scores that could be applicable for immune therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The overall 5-year survival rate in this study reach up to 64%, which is much lower than those reported. 15,16 The logic explanation to these findings is the high proportions of advanced stage population presented at RSCM. Almost 60% of population presented in a locally advanced and metastatic stage; both were associated with poor survival rate (85% and 38%, respectively) compared to those of the earlier stage (96%).…”
Section: Discussionmentioning
confidence: 99%